2004
DOI: 10.1080/03079450310001636237a
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of avian leukosis virus subgroup J in commercial layer flocks in China

Abstract: Mortality from myeloid leukosis was observed in commercial layers from 12 farms in northern China. Affected chickens were extremely thin and dehydrated, bleeding occurred in feather follicles and claws, combs were pale and anaemic, phalanges were swollen, and many yellowish-white tumours were seen on the visceral surface of the sternum. Focal tumour cells, with spherical eosinophilic granules in the cytoplasm, were found in the liver, spleen, kidney, ovary, oviduct, lung, bone marrow, proventriculus and gut by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 5 publications
5
63
0
1
Order By: Relevance
“…However, ALV-J infections started to spread in other types of chickens, such as the Taiwan native breed crossbred with imported white meat-type breeders (Thu et al ., 2003) and old fancy chicken breeds in The Netherlands (de Witt et al ., 2004). In mainland China, subgroup J avian leukosis cases with high mortality occurred even in some commercial layer farms (Xu et al ., 2004) and in some flocks of local chicken breeds (Chen et al ., 2005) in the northern part of China. In both reports from China, the diagnosis was made by histological studies and PCR product analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ALV-J infections started to spread in other types of chickens, such as the Taiwan native breed crossbred with imported white meat-type breeders (Thu et al ., 2003) and old fancy chicken breeds in The Netherlands (de Witt et al ., 2004). In mainland China, subgroup J avian leukosis cases with high mortality occurred even in some commercial layer farms (Xu et al ., 2004) and in some flocks of local chicken breeds (Chen et al ., 2005) in the northern part of China. In both reports from China, the diagnosis was made by histological studies and PCR product analysis.…”
Section: Discussionmentioning
confidence: 99%
“…There were also some reports of subgroup J myelocytomatosis cases in commercial layer flocks and ''yellow'' chicken flocks of local breeds in northern China in recent years (Xu et al ., 2004;Chen et al ., 2005). They were diagnosed by histopathological examination and polymerase chain reaction (PCR) products, but no virus was isolated.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worthy of note that neoplastic lesions on the rib cage was observed in 3.42% of the cases of avian neoplastic diseases. This lesion is thought to be pathogmonic for myeloid leukosis (Xu et al, 2004). This study has shown that the prevalence of avian neoplastic disease, especially MD, is on the rise and measures must be put in place to arrest this dangerous trend.…”
Section: Discussionmentioning
confidence: 99%
“…For two decades was assumed that ALV-J was restricted in meat type chickens. Although egg-type chickens have been experimentally infected with ALV-J to induce tumors (Payne et al, 1992a) the first field case of ALV-J infection in egg type chickens was reported in China 2004 (Gingerich et al, 2002;Xu et al, 2004). The ALV-J virus was isolated in meat type chickens in Egypt in 2000 (Aly, 2000).…”
Section: Introductionmentioning
confidence: 99%